BELAJAR MENYENANGKAN - Simorangkir, Melda (Jurnal Dinamika Pendidikan, 2015)
A civilization will decrease if there is demoralization in society. Many experts, philosophers and sages say that the moral factor (morality) is the main thing that should be built first in order to build a society that is orderly, safe, and prosperous. One of the main obligations that must be run by parents and educators is to preserve and teach moral values to our children. Instilled moral values will shape the character that is an important foundation for the formation of a civilized society and prosperous. First we believe once that three basic capital that belongs to Indonesia as a large area, abundant natural resources and large population, will bring our nation becomes prosperous. But it turned out everything was not proven. Even if we look at countries